Digital Governance for Sustainable Educational Transformation: Evaluating Merdeka Curriculum Implementation through PMO E-Instruments in Indonesia - Ulfah Irani Zakaria; Rosmiati Rosmiati (PAEDAGOGIA, 2025)
This study investigates the pivotal role of Project Management Office (PMO) e-instruments in evaluating the implementation of the Merdeka Curriculum (Merdeka Curriculum) within Indonesia's Driving School ‘Sekolah Penggerak’ program. The research was initiated by the critical need to ensure consistency and quality in curriculum application across diverse educational contexts, aligning with Indonesia's ongoing national educational transformation. Employing a descriptive qualitative-quantitative approach, the study involved four primary schools designated as Sekolah Penggerak, with principals and teaching staff engaging in structured assessments using the PMO e-instruments. Key findings indicated moderate performance in planning and instructional execution across most participating schools, while leadership practices demonstrated notable variability. Collaborative aspects of the curriculum, particularly project-based learning and community involvement, consistently exhibited stronger outcomes. Conversely, areas such as reflection, evaluation, and student-centered learning were identified as requiring further development. The PMO e-instrument proved to be an effective diagnostic and developmental tool, empowering school leaders to make evidence-based decisions for enhancing curriculum delivery. These findings underscore the profound importance of continuous capacity-building for school leaders to fully actualize the transformative goals of the Merdeka Curriculum. The diagnostic capability of the PMO e-instrument directly facilitates data-driven decision-making, which is a core objective of integrating such digital systems into educational management. This allows for precise identification of areas needing improvement. These findings underscore the importance of continuous capacity-building for school leaders to fully actualize the goals of the Merdeka Curriculum.